2020
DOI: 10.3390/curroncol28010009
|View full text |Cite
|
Sign up to set email alerts
|

Lung Metastasis Probability in Ewing Sarcoma: A Nomogram Based on the SEER Database

Abstract: Background. Up to now, an accurate nomogram to predict the lung metastasis probability in Ewing sarcoma (ES) at initial diagnosis is lacking. Our objective was to construct and validate a nomogram for the prediction of lung metastasis in ES patients. Methods. A total of 1157 patients with ES from the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively collected. The predictors of lung metastasis were identified via the least absolute shrinkage and selection operator (LASSO) and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Of the 94 studies that shared a major study question with at least one other study, 35% (33 of 94) reported discordant key findings concerning 10 study questions [1, 6, 8, 11‐13, 18, 23, 26, 29, 36, 39‐41, 44, 49, 53, 59, 63, 67, 68, 72, 79, 83, 93, 95, 98‐100, 106, 109‐111] (Table 2), 29% (27 of 94) reported mixed key findings concerning six study questions [3, 7, 15, 19, 22, 25, 27, 28, 30, 35‐37, 43, 45, 47, 50, 56, 75, 76, 82, 88‐91, 103, 104, 107] (Table 3), and 44% (41 of 94) reported concordant key findings concerning 12 study questions [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112] (Table 4). Of the 299 studies in total, 20% (59 of 299) reported discordant or mixed findings [1, 3, 6‐8, 11‐13, 15, 18, 19, 22, 23, 25‐30, 35‐37, 39‐41, 43‐45, 47, 49, 50, 53, 56, 59, 63, 67, 68, 72, 75, 76, 79, 82, 83, 88‐91, 93, 95, 98‐100, 103, 104, 106, 107, 109‐111] and 14% (41 of 299) reported concordant findings [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112]. Examples of topics with discordant or mixed findings include the effect of radiation on survival in several sarcoma types and the influence of race on treatment and survival.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 94 studies that shared a major study question with at least one other study, 35% (33 of 94) reported discordant key findings concerning 10 study questions [1, 6, 8, 11‐13, 18, 23, 26, 29, 36, 39‐41, 44, 49, 53, 59, 63, 67, 68, 72, 79, 83, 93, 95, 98‐100, 106, 109‐111] (Table 2), 29% (27 of 94) reported mixed key findings concerning six study questions [3, 7, 15, 19, 22, 25, 27, 28, 30, 35‐37, 43, 45, 47, 50, 56, 75, 76, 82, 88‐91, 103, 104, 107] (Table 3), and 44% (41 of 94) reported concordant key findings concerning 12 study questions [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112] (Table 4). Of the 299 studies in total, 20% (59 of 299) reported discordant or mixed findings [1, 3, 6‐8, 11‐13, 15, 18, 19, 22, 23, 25‐30, 35‐37, 39‐41, 43‐45, 47, 49, 50, 53, 56, 59, 63, 67, 68, 72, 75, 76, 79, 82, 83, 88‐91, 93, 95, 98‐100, 103, 104, 106, 107, 109‐111] and 14% (41 of 299) reported concordant findings [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112]. Examples of topics with discordant or mixed findings include the effect of radiation on survival in several sarcoma types and the influence of race on treatment and survival.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies reported that gender was not a risk factor for pulmonary metastases of ES, larger tumors had a higher chance of pulmonary metastases, and the results of age, and primary location were controversial. Li et al found that surgery was a protective factor against pulmonary metastases and chemotherapy had no signi cant difference between MT and non-MT groups (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…T stage is one of the prognostic factors in our nomogram, and some previous studies have shown that a larger tumor volume is related to poor prognosis ( 28 30 ). M stage is also a prognostic factor, representing whether metastasis will affect the patient's OS.…”
Section: Discussionmentioning
confidence: 99%
“…Wang J built a model for predicting ES mortality using least absolute shrinkage and selection operator (LASSO) analysis and multivariate logistic analysis with five factors (age, tumor size, primary site, tumor extension, and other site metastasis). However, that nomogram does not include treatment approach ( 28 ). Chen L created a nomogram to predict the OS of pelvic ES with four factors (age, race, tumor stage, and surgery) ( 9 ).…”
Section: Discussionmentioning
confidence: 99%